From Istanbul to Aceh: Strategic Transfers of Power, Technology, and Expertise in the 16th–17th Centuries - Lukman Hakim; Andi Rahman; Tania Anjani Maulana (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
This study investigates the Ottoman Empire’s substantial contribution to Acehnese development during the sixteenth and seventeenth centuries, emphasizing how strategic alliances, military expertise, and technological transfers enabled Aceh to resist Portuguese expansion and establish itself as a leading maritime power in Southeast Asia. Utilizing correspondence and historical records from both Acehnese and Ottoman sources, the research identifies key areas of collaboration, including the establishment of military academies, weapons production, and warship construction. In addition to military cooperation, the study underscores the Ottoman Empire’s influence on Aceh’s intellectual and governmental spheres through the involvement of Ottoman-trained scholars in the Aceh Sultanate, the adoption of administrative practices, and the enhancement of Aceh’s political legitimacy as an Islamic sultanate. Employing a historical–analytical methodology, the study draws on primary sources such as De Hikajat Atjeh, Adat Aceh, Hikayat Meukuta Alam, Ottoman imperial archives, and European travel narratives. The findings demonstrate that the Ottoman Empire played a significant role in transforming Aceh into a prominent military and intellectual center. This partnership consolidated Aceh’s maritime supremacy, reinforced its governmental structures, and protected its sovereignty. The Ottoman–Aceh alliance exemplifies broader patterns of cross-cultural exchange within the Islamic world and highlights the geopolitical significance of such strategic relationships.